Relationship between Benzene Concentrations with Erythrocyte, Hemoglobin, and Health Complaints of Workers in Surabaya Printing Industry - Maria Ayu Dwi Bestari1 , Abdul Rohim Tualeka2 , Putri Ayuni Alayyannur3 , Shintia Yunita Arini4 , Sy (Institute of Medico-legal Publications Pvt Ltd, 2020)
Printing industry uses a lot of raw materials that contain benzene in the production process. Exposure tobenzene can cause haematological effects that affect the production of blood cells. The purpose of thisstudy was to determine the relationship between benzene concentrations with erythrocytes, hemoglobin, andhealth complaints among workers in Surabaya Printing Industry. This research was conducted in PrintingX Surabaya. This research is observational, quantitative approach, and cross-sectional. The respondents inthis study were 19 people. The variables studied were the concentration of benzene in the air, erythrocytes,hemoglobin, and health complaints among workers at Printing X Surabaya. Data analysis using Spearmanrank correlation test. Measurement of the concentration of benzene in the air exceeds the Threshold LimitValue. There were 5 respondents had erythrocyte level above the normal and 1 respondent had hemoglobinlevel below the normal. There was a quite significant and positive relationship between the concentrationof benzene in the air and erythrocytes (p=0.033). But there was no significant relationship between theconcentration of benzene in the air and hemoglobin (p=0.158). Health complaints experienced by workersin Printing X Surabaya included coughing, headaches, and shortness of breath. There is a fairly strongrelationship between benzene concentrations and erythrocytes but there is no relationship between benzeneconcentration and hemoglobin.